VET Qualifications versus Bachelor Degrees? Recruitment at the Intermediate Qualification Level : Case Studies from Germany, England and Switzerland - Hippach-Schneider, Ute [Verfasser]; Weigel, Tanja [Verfasser] (My University, 2012)
"The German and Swiss economies value skilled work highly and initial vocational education and training (IVET) has been the predominant traditional pathway into such work. However, concerns about a more 'knowledge-based society' and the 'academic shift in the labour market' are starting to undermine the status associated with those who complete IVET pathways and these former trainees also face competition from graduates from the relatively new Bachelor programmes in Switzerland and Germany. An international project investigated whether these developments pose a threat to developed IVET systems and whether companies are changing their recruitment strategies and how they rate the status of IVET. The findings from Germany and Switzerland were compared with the situation in England, the home of two-phase HE structures along with a very different tradition of vocational training. The findings from individual case studies in England, Germany and Switzerland are presented here, with the focus on the expectations of companies towards applicants with experience of IVET or Bachelor's degrees." (Autorenreferat; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; P 2.4 Facharbeiter / Gesellen; P 2.6 Hochschulabsolventen; I 2.2.1 Westeuropa; Personalgewinnung; Ausbildungsabschluss; Bachelor; Internationaler Vergleich; Schweiz; Bundesrepublik Deutschland; England